Comparação de métodos de limpeza na formação de Eucalyptus alba (Blume) Reinw., E. saligna Sm. e E. botryoides Sm - Mauro Brandi, Renato; de Barros , Nairam Félix; Candido, José Flávio (Revista Ceres, 2025)
A study to measure the effect of five weeding procedures on performance of Eucalyptus seedlings of three species (E. alba, E. saligna and E. botryoides) was conducted over a 27 month period in Viçosa, Minas Gerais. The land used was a latossol type with 25 percent slope and covered by Imperata brasiliensis aad Melinis minutiflora the predominate vegetation. Weedings were performed five times at wich time the terminal growth and labor-cost measurements were also made.